Perceived Stress and Variation of Blood Pressure Among Re-Rolling Steel Mill Workers - Rahman, Md Arafat; Hossain, Irin (Journal of Preventive and Social Medicine, 2025)
Background: The steel industry is crucial to global infrastructure and economic growth, with rising demands fueled by urbanization and energy needs. In Bangladesh, the sector has grown significantly since the 1990s, but health risks for workers, such as stress-related disorders and hypertension, remain under-addressed. This study evaluates stress levels and blood pressure variations among re-rolling steel mill workers in Bangladesh, with the goal of guiding interventions to enhance worker health and occupational safety. Methods: A cross-sectional study was carried out in a re-rolling steel mill in the Thana area of Bangladesh to assess stress levels and blood pressure variations among workers with at least one year of experience. The study involved protocol development, data collection, and final report submission. A semi-structured questionnaire was used to gather socio-demographic information, perceived stress levels, and blood pressure measurements. Data analysis was performed using descriptive statistics, chi-square tests, and statistical inference, with ethical considerations carefully observed throughout the study. Results: The study surveyed respondents aged 19-52 years with a mean age of 34.72±8.948 years, predominantly Muslim with a majority completing primary education. Most (48.8%) had monthly income with 8,000 to 12,000 taka while mechanical workers being the largest of working sections (41.8%). The study revealed that the majority of respondents (53%) experienced moderate perceived stress, while 45.6% reported low levels of stress. A small proportion of respondents, comprising only 1.4%, reported experiencing highly perceived stress. Conclusion: This study enhances our comprehension of the intricate relationship between occupational factors, psychosocial stress, and cardiovascular health outcomes in industrial environments, offering valuable insights for workplace health promotion and research. JOPSOM 2023; 42(2): 18-22